A case study of the development of an ESL learner's speaking skills through instructional debate - Amiri, Farzaneh; Othman, Moomala; Jahedi, Maryam (Center for Promoting Ideas, 2017)
This study aimed to describe the implementation of debate activities in teaching English to Malaysian secondary students which can enhance students’ speaking skills. Moreover, through observing a Form One student, it was tried to identify the strategies used to compete in classroom debates and to describe the development of the participant’s speaking skills through debates. The study found that debate activities had an impact on the participants through improving collaborative skills, raising awareness of speakers’ roles and guiding participants via prepared texts. Besides, the main communicative strategies employed by the participant were compensatory and avoidance strategies. The result has also shown the improvement of the participant’s speaking skills after five rounds of debate activities.